Superior mechanical properties of a high temperature Co-based superalloy fabricated by laser powder bed fusion - Liuhao Miao; Huiliang Wei; Jiashun Yue; Rong Chen; Yuanhong Qian; Xiaopeng Li; Zhiguang Zhu; Tingting Liu; Wenhe Liao (Additive Manufacturing Letters)
Laser powder bed fusion (LPBF) of high temperature superalloys with superior mechanical properties are highly desired. However, the correlations between the process, microstructure and ambient/high temperature mechanical properties for the typical Co-based superalloy Haynes 188 remain unclear. In this work, the process development, the ambient and high temperature mechanical properties for LPBF of Haynes 188 were systematically explored. Samples with relative density over 99.9 % were achieved. Unprecedented ambient temperature strength-ductility were obtained, with yield strength of 756 MPa, tensile strength of 1067 MPa, and elongation of 60.2 %, respectively. Moreover, high temperature mechanical properties such as the steady-state creep rate of 1.04×10−4 s⁻¹ at 750 °C and 270 MPa were firstly reported. Additionally, the yield strength of Haynes 188 at 980 °C reached 276 MPa. Microstructural analysis revealed that nano-scale M6C/M23C6 carbides pinned dislocations, while dense dislocation networks and refined sub-grains suppressed dynamic recovery. The obtained achievements can provide valuable insights for additive manufacturing of complex and high-performance Haynes 188 components.